pH-dependent endocytosis mechanisms for influenza A and SARS-coronavirus - Aganovic, Amar (Frontiers in Microbiology, 2023)
The ongoing SARS-CoV-2 pandemics and the Influenza epidemics have revived the interest in understanding how these highly contagious enveloped viruses respond to alterations in the physicochemical properties of their microenvironment. By understanding the mechanisms and conditions by which viruses exploit the pH environment of the host cell during endocytosis, we can gain a better understanding of how they respond to pH-regulated anti-viral therapies but also pH-induced changes in extracellular environments. This review provides a detailed explanation of the pH-dependent viral structural changes preceding and initiating viral disassembly during endocytosis for influenza A (IAV) and SARS coronaviruses. While there are similarities in in the pH-regulated patterns leading to fusion, the mechanisms and pH activation differ. In terms of fusion activity, the measured activation pH values for IAV, across all subtypes and species, vary between approximately 5.0 to 6.0, while SARS-coronavirus necessitates a lower pH of 6.0 or less. The main difference between the pH-dependent endocytic pathways is that the SARS-Coronavirus, unlike IAV, require the presence of specific pH-sensitive enzymes (cathepsin L) during endosomal transport. Conversely, the conformational changes in the IAV virus under acidic conditions in endosomes occur due to the specific envelope protein residues and protein ion channels getting protonated by H+ ions. Despite extensive research over several decades, comprehending the pH-triggered conformational alterations of viruses still poses a significant challenge. The precise mechanisms of protonation mechanisms of certain envelope proteins during endosomal transport for both viruses remain incompletely understood. In absence of evidence, further research is needed.